COMPARATIVE STUDY OF THE STATE OF LITERACY IN NIGERIA AND CUBA - Yusuf Murtala Akanbi; Ladan Babangida; Idris Usman Abba; Auwalu Halilu (European Scientific Journal, ESJ, 2013)
Literacy has been identified as an important instrument through which any country can attain development. It is on this belief that government and people of Nigeria have taken the issue of how to increase literacy rates among children and adults as an important one. Despite this, Nigeria is among E-9 countries, which are countries that account for more than 50% of the world’s population and have the highest number of illiterates when her counterpart in other developing country for example Cuba has attained almost 100% literacy rate. It is against this background that this paper examines comparative analyses of the status of literacy in Nigeria and Cuba. Factors responsible for the state of literacy in the two countries were indentified and analysed. The paper concludes that Nigeria can learn from Cuba in order to improve her literacy status.